Improving Digital Literacy of Grass Jelly (Cincau) based MSMEs through Digital Marketing and Website Management Training - Ayu Ningtyas, Mastuty; Setiawan, Yohanes; Yuniar Rochmah, Wachda; Akhsani Setyo Prayoga, Riza; Anjas Ardiansyah, Muhammad; Ichsan Khoirudin, Machfud; Rashid Syaputra, Muhammad; Dwi Ardhani, Yuniar (Universitas Ahmad Dahlan, 2025)
Background: Grass Jelly Village (Cincau) based Micro, Small, and Medium-sized Enterprises (MSMEs) in Surabaya, Indonesia, has started digitalization by building a website profile to promote their products. However, they need help managing the website and selling their brands since they have lower digital literacy resources, and their website only has a single admin. Contribution: This community service program contributes to enhancing digital literacy in Grass Jelly Village by providing structured training in digital marketing and website management, aiming to empower local residents in utilizing digital platforms for economic and social development. Method: The course process involves three stages: preparation, implementation, and evaluation. Preparation includes analyzing requirements and designing course materials, followed by practical implementation, and evaluation consists of evaluating the course through feedback and evaluation forms. Results: Based on the satisfaction survey on digital marketing training received a score of 89.33%, copywriting training received a score of 85%, website training received a score of 90.66%. Then there is a satisfaction survey on the speaker by getting a score of 92%. Conclusion: The digitalization training for Grass Jelly Village's MSMEs was highly effective, resulting in enhanced digital literacy and improved business practices. The program's long-term sustainability is supported by follow-up strategies, including forming a dedicated digital team and ongoing mentorship.